Objective image analysis of non-magnifying image-enhanced endoscopy for diagnosis of small depressed early gastric cancers - Watari, Jiro; Kobayashi, Masaya; Nakai, Keisuke; Ito, Chiyomi; Tamura, Akio; Ogawa, Tomohiro; Yamasaki, Takahisa; Okugawa, Takuya; Kondo, Takashi; Kono, Tomoaki; Tozawa, Katsuyuki; Tomita, Toshihiko; Oshima, Tadayuki; Fukui, Hirokazu; Morimoto, Takeshi; Miwa, Hiroto (Endoscopy International Open, 2018)
Background Gastric cancers (GC) after H. pylori eradication are difficult to diagnose even by magnifying narrow-band imaging (NBI) or blue laser imaging (BLI) endoscopy. Little is known with regard to non-magnifying (NM)-NBI/BLI for early GC so we examined the efficacy of NM-NBI/BLI for early GC diagnosis.Methods We retrospectively analyzed the images of 29 small (≤ 1 cm) intramucosal GC that had been treated with endoscopic submucosal dissection and 137 benign depressed lesions (BDLs). The brightness and shape of the GCs and BDLs by NM-NBI/BLI were assessed with ImageJ software.Results The NBI/BLI-index, which indicates the brightness of NBI/BLI for visualization, was significantly higher in GC than BDLs in both the H. pylori-infected (P = 0.009) and -eradicated group (P < 0.0001), indicating that GC exhibited brighter colors than the normal surrounding mucosa. The C-index, which refers to the circularity of the lesion, was also significantly higher in GC than BDLs in both H. pylori-infected (P = 0.006) and -eradicated cases (P = 0.004). Based on receiver-operating characteristic curve analysis, cutoff values for the NBI/BLI- and C-indices for GC were 1.04 and 0.58 in the H. pylori-infected cases, and 0.98 and 0.64 in the H. pylori-eradicated cases. With the reference value of the NBI/BLI-index set at ≥ 0.69 with the C-index at ≥ 0.21 in the H. pylori-infected and the NBI/BLI-index at ≥ 0.80 with the C-index at ≥ 0.32 in the H. pylori-eradicated cases, both the sensitivity and negative predictive value for early GC were 100 %. A high NBI/BLI-index tended to be associated with a wide length of the intervening part histologically in the H. pylori-eradicated cases (P = 0.09).Conclusions The small depressed-type early GC had brighter color and rounder shape compared to BDLs in both H. pylori-infected and -eradicated cases. The NBI/BLI- and C-indices calculated by the image analysis may facilitate identification of small depressed-type GC.